Cold exposure down-regulates immune response pathways in ferret aortic perivascular adipose tissue - Reynés, Bàrbara; van Schothorst, Evert M.; García-Ruiz, Estefanía; Keijer, Jaap; Palou, Andreu; Oliver, Paula (Thrombosis and Haemostasis, 2017)
Perivascular adipose tissue (PVAT) surrounds blood vessels and releases paracrine factors, such as cytokines, which regulate local inflammation. The inflammatory state of PVAT has an important role in vascular disease; a pro-inflammatory state has been related with atherosclerosis development, whereas an anti-inflammatory one is protective. Cold exposure beneficially affects immune responses and, could thus impact the pathogenesis of cardiovascular diseases. In this study, we investigated the effects of one-week of cold exposure at 4°C of ferrets on aortic PVAT (aPVAT) versus subcutaneous adipose tissue. Ferrets were used because of the similarity of their adipose tissues to those of humans. A ferret-specific Agilent microarray was designed to cover the complete ferret genome and global gene expression analysis was performed. The data showed that cold exposure altered gene expression mainly in aPVAT. Most of the regulated genes were associated with cell cycle, immune response and gene expression regulation, and were mainly down-regulated. Regarding the effects on immune response, cold acclimation decreased the expression of genes involved in antigen recognition and presentation, cytokine signalling and immune system maturation and activation. This immunosuppressive gene expression pattern was depot-specific, as it was not observed in the inguinal subcutaneous depot. Interestingly, this depression in immune response related genes was also evident in peripheral blood mononuclear cells (PBMC). In conclusion, these results reveal that cold acclimation produces an inhibition of immune response-related pathways in aPVAT, reflected in PBMC, indicative of an anti-inflammatory response, which can potentially be exploited for the enhancement or maintenance of cardiovascular health.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Mustela putorius furo; transcriptomics; immune response; cardiovascular diseases; peripheral blood mononuclear cells